PROFILE OF TRANSFUSION REACTIONS RELATED TO THE INFUSION OF HEMATOPOIETIC CELL IN A PEDIATRIC CENTER - ECDS Pirolli; RAF Tutumi; FW Garcia; R Nomura; ER Pinto; MJ Piloni; JLM Bach; C Bonfim (Hematology, Transfusion and Cell Therapy)
Introduction: Hematopoietic Cell Transplantation (HCT) is utilized as a significant therapeutic option for treating numerous malignant and non-malignant diseases. During the infusion of Hematopoietic Cell (HC), patients may experience adverse reactions related to ABO/Rh incompatibility, which can be categorized as mild, moderate, or severe, with immediate reactions occurring up to 24 hours after infusion and delayed reactions thereafter. These reactions can range from cutaneous rash, hypertension, hemoglobinuria, anaphylaxis, sepsis, and even death. Objectives: To analyze the profile and events of patients who received HC infusion and developed adverse reactions. Method: A quantitative retrospective study with a cross-sectional design was conducted through medical record analysis. Patients aged between 0 and 18 years who underwent allogeneic HC at a pediatric center between January 2022 and December 2023 were included. Results: A total of 108 HC infusions were conducted during the analyzed period; 37% (n = 40) had malignant diseases, 31% (n = 23) had hemoglobinopathies, 17% (n = 18) had immunodeficiencies, 13% (n = 14) had inborn errors of metabolism, and 12% (n = 13) had bone marrow failures. In 50% (n = 54) of cases, the donors were haploidentical, 32% (n = 35) were unrelated, and 18% (n = 19) were compatible related. The cell sources were peripheral blood 10% (n = 11), bone marrow 89% (n = 96), and umbilical cord blood 1% (n = 1). ABO/Rh incompatibility was found in 56% (n = 60), with 38% (n = 23) having minor incompatibility, 28% (n = 17) major incompatibility, 22% (n = 13) Rh incompatibility, and 12% (n = 7) bidirectional incompatibility. In 31% (n = 34) of patients, the marrow received some form of treatment prior to infusion. Immediate adverse reactions were observed in 31% (n = 34) of patients; 68% (n = 23) experienced hypertension, 26% (n = 9) had a cutaneous rash, and 9% (n = 3) had hemoglobinuria. Treatment was administered to 38% (n = 13) of patients who experienced a reaction. Regarding the severity of reactions, 18% (n = 6) required urgent interventions, such as pausing marrow infusion and the use of antihistamines and corticosteroids. The median infusion time for patients who experienced a reaction was 7 hours, whereas for patients without any reaction, the median was 4 hours. Conclusion: Pre-treatment of HC did not exclude the occurrence of reactions during infusion, emphasizing the importance of knowledge of infusion protocols and, especially, early recognition of signs and symptoms by nursing professionals. Rapid and appropriate treatment are crucial for a favorable outcome for all patients, especially in cases of severe reactions. Based on the presented scenario, the results supported improvements in care processes, as well as the provision of a specific kit for transfusion reactions that is currently in the implementation phase in the unit, aiming to make the control of adverse transfusion-related events more efficient and effective.